Development of CLASSALI:An Online Learning Tool and Academic Performance Report for Makati Public Elementary Schools - Biñas, Victor Jet P.; Carreon, Mark Justin Z.; Concilles, Marjorie P.; Congzon, Janice Pola D.; Mansueto, Christian Michael M. (International Journal of Computing Sciences Research, 2022)
Purpose – The main focus of the study is to develop an asynchronous framework ready for online classes of Makati Public Elementary Schools with Academic Performance Report to help users identify students at academic risk and adjust educational strategies to meet student's academic needs.CLASSALI is equipped with five major features namely: (1) Virtual Classroom, (2) Online Quiz, (3) Grading System, (4) CLASSALI Forum, and (5) Data Analytics Reports. Method –Researchers conduct an online assessment that has been tested by fifteen IT Practitioners and fifteen Non-IT Participants including admin, teachers, students, and parents. The data collected during the evaluation were computed for the analysis and efficiency of the system. Results – The system gathered reviews mostly with “Excellent” remarks. Conclusion – The system was found relevant nowadays since a new normal setting (i.e., pure online classes) due to the COVID-19 pandemic. Recommendations – In the future analysis, some research points should be given more attention. First and foremost, the developed learning management system should be implemented in other schools in the Philippines. In the future to further examine the stability and generalization of the developed learning management system. Practical Implications – It helps significant users such as teachers, school administrators, and parents rapidly identify students at academic risk and adjust educational strategies to meet students' needs.